ANALISIS TRANSFORMASI DIGITAL UNTUK MENINGKATKAN DAYA SAING PERUSAHAAN ASURANSI JIWA - Nanda, Andesna; Napitupulu, Reimond; Wulandari, Vika (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the role of digital transformation in enhancing the competitiveness of life insurance companies. Digital transformation has become a critical strategy in responding to changing customer behavior, increasing industry competition, and rapid technological advancements. The research employs a systematic literature review method by examining relevant academic articles and industry reports on digital transformation and life insurance. The findings indicate that the adoption of digital technologies, such as process automation, data analytics, and digital service platforms, contributes to improved operational efficiency, service quality, and customer experience. However, the success of digital transformation largely depends on human resource readiness and strong managerial support.